2019
DOI: 10.1109/tgrs.2018.2886998
|View full text |Cite
|
Sign up to set email alerts
|

Removing Intra-1-Hz Covariant Error to Improve Altimetric Profiles of $\sigma^{0}$ and Sea Surface Height

Abstract: Waveform retracking is the process by which a simple mathematical model is fitted to altimeter returns. Over the ocean the waveform location, amplitude and shape can be fitted by models with 3-5 free parameters, which may in turn be linked to geophysical properties of the surface of interest principally sea surface height, wave height and normalized backscatter strength (0 , related to wind speed). However random multiplicative noise, which is due to the summation of power from multiple differently orientated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Similarly, for those algorithms that fit both amplitude (σ 0 ) and mispointing (ψ 2 ), which are both terms related to the power distribution in the trailing edge (see Figure 1b), there is a strong connection between their errors [7,8]. Quartly [7] showed how this property could be used to significantly improve the σ 0 estimates from the MLE-4 algorithm and, more recently, Zaron and deCarvalho [9] and then Quartly et al [10] have demonstrated how the Hs data can be utilised to provide smoother (more realistic) variations in range, and thus ultimately in sea level. Here, we take those ideas and explore the potential for the range information to be used instead to improve the quality of wave height estimates.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Similarly, for those algorithms that fit both amplitude (σ 0 ) and mispointing (ψ 2 ), which are both terms related to the power distribution in the trailing edge (see Figure 1b), there is a strong connection between their errors [7,8]. Quartly [7] showed how this property could be used to significantly improve the σ 0 estimates from the MLE-4 algorithm and, more recently, Zaron and deCarvalho [9] and then Quartly et al [10] have demonstrated how the Hs data can be utilised to provide smoother (more realistic) variations in range, and thus ultimately in sea level. Here, we take those ideas and explore the potential for the range information to be used instead to improve the quality of wave height estimates.…”
Section: Introductionmentioning
confidence: 80%
“…Since both estimates of range and wave height are derived from a few waveform bins on the leading edge of an LRM waveform, their estimates are sensitive to the existence of fading noise affecting the power levels within this section of the waveform (Figure 1b). Sandwell and Smith [11] showed that there was a correlation between the noise-induced anomalies in these two parameters, and Zaron and deCarvalho [9] and Quartly et al [10] have used this empirical connection to reduce the errors in range. The present paper demonstrates that the reverse procedure is equally applicable: using local anomalies in ζ (altitude minus range) to reduce the associated errors in SWH.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations